2021
DOI: 10.3390/w13162215
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Biota Is Not Exempt from Coronavirus Infections: An Overview

Abstract: Coronaviruses are pathogens recognized for having an animal origin, commonly associated with terrestrial environments. However, in a few cases, there are reports of their presence in aquatic organisms like fish, frogs, waterfowl, and marine mammals. None of these cases has led to human health effects when contact with these infected organisms has taken place, whether they were alive or dead. Aquatic birds seem to be the main group carrying and circulating these types of viruses among healthy bird populations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…The global spread of the coronavirus may affect not only the ecosystems and urban infrastructures but also people's lifestyles. Several studies have already reported on the effect on ecosystems and urban infrastructure [1][2][3]. People's behaviors and lifestyles will also change due to the pandemic; if these behaviors remain changed, the design of urban infrastructure and housing facilities will be affected.…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of the coronavirus may affect not only the ecosystems and urban infrastructures but also people's lifestyles. Several studies have already reported on the effect on ecosystems and urban infrastructure [1][2][3]. People's behaviors and lifestyles will also change due to the pandemic; if these behaviors remain changed, the design of urban infrastructure and housing facilities will be affected.…”
Section: Introductionmentioning
confidence: 99%